2019
DOI: 10.1111/ner.12963
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Effect of Repeated Bolus or Continuous Intrathecal Infusion of Morphine on Spinal Mass Formation in the Dog

Abstract: Background We determined whether intrathecally delivering the same daily dose of morphine (MS) at a fixed concentration of 25 mg/mL by periodic boluses versus continuous infusion would reduce intrathecal mass (IMs) formation in dogs. Methods Adult dogs (hound cross, n = 32) were implanted with intrathecal catheters connected to SynchroMed II infusion pumps. Animals were randomly assigned to receive infusion of 0.48 mL/day of saline or MS dosing (12 mg/day at 25 mg/mL) as boluses: x1 (q24hour), x2 (q12hour), x4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Accordingly, chronic administration with drug pumps may be governed by conditions of natural oscillation (phase-2) for its entire time course discussed below. For more recent developments for effective infusion protocols from drug pumps we refer to the work by Yaksh [33].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, chronic administration with drug pumps may be governed by conditions of natural oscillation (phase-2) for its entire time course discussed below. For more recent developments for effective infusion protocols from drug pumps we refer to the work by Yaksh [33].…”
Section: Discussionmentioning
confidence: 99%
“…In recent work, it has been shown that delivering a fixed volume of concentrated morphine as a continuous infusion (20 µL/h) leads to spinal masses. In contrast, delivering the same total dose/volume in multiple-divided fast boluses resulting in greater local movement reduces the incidence of such masses (175).…”
Section: Spinal Drug Activity: Role Of Local Redistributionmentioning
confidence: 99%
“…The incidence of granuloma has been reported to be significantly less frequent with bolus administration compared to a continuous flow rate, meaning that bolusing increases local pericatheter dilution (but not rostral distribution of drugs) (175).…”
Section: Delivery Programming and Outcomementioning
confidence: 99%
See 2 more Smart Citations